Light-induced water oxidation catalyzed by an oxido-bridged triruthenium complex with a Ru–O–Ru–O–Ru motif. Issue 51 (6th June 2016) - Tsubonouchi, Yuta; Lin, Shu; Parent, Alexander R.; Brudvig, Gary W.; Sakai, Ken
Abstract : A μ-oxido-bridged triruthenium complex (RuT 2+ ), formed by air oxidation of a previously reported monoruthenium water-oxidation catalyst (WOC), serves as an efficient photochemical WOC with the turnover frequency (TOF) and turnover number (TON) 0.90 s −1 and 610, respectively. Abstract : A μ-oxido-bridged triruthenium complex (RuT 2+ ), formed by air-oxidation of a previously reported monoruthenium water oxidation catalyst (WOC), serves as an efficient photochemical WOC with the turnover frequency (TOF) and turnover number (TON) 0.90 s −1 and 610, respectively. The crystal structures ofRuT 2+ and its one-electron oxidizedRuT 3+ are also reported.